Preferences for distributional impacts of climate policy - Lea Skræp Svenningsen; Bo Jellesmark Thorsen (University of Copenhagen, Department of Food and Resource Economics (IFRO), 2017)
What role do people think distributional aspects should play in design of climate policy? The literature assessing climate policies has shown that assumptions regarding peoples' distributional preferences for climate change policy impacts are central for policy assessment, but empirical evidence for such preferences is lacking. We design a discrete choice experiment that varies how climate policies affect the income of people living in the future in three geographical regions. The experiment is implemented on a representative sample of the Danish population and preferences are modelled in a latent class model. Our results show that i) a small majority of Danes expresses preferences for climate policies consistent with inequity aversion, ii) a group expresses preferences resembling simple warm glow, while iii) a small group prefers not to support additional climate policies. Finally a somewhat larger group expresses some form of distributional preferences, but shows positive preferences for costs, suggesting that responses could be influenced by strategic behaviour and over-signalling of commitment. Our results provide support for the inclusion of social preferences regarding distributional effects of climate change policies in policy assessments, and hence for the significant impact on policy this inclusion have.
Keywords: D30; H41; Q51; Q54; 330; choice experiment; social preferences; inequity aversion; warm glow; altruism; climate change impacts; latent class; social cost of carbon